2015
DOI: 10.1007/s10916-015-0214-6
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Lung Segmentation Using Control Feedback System: Morphology and Texture Paradigm

Abstract: Interstitial Lung Disease (ILD) encompasses a wide array of diseases that share some common radiologic characteristics. When diagnosing such diseases, radiologists can be affected by heavy workload and fatigue thus decreasing diagnostic accuracy. Automatic segmentation is the first step in implementing a Computer Aided Diagnosis (CAD) that will help radiologists to improve diagnostic accuracy thereby reducing manual interpretation. Automatic segmentation proposed uses an initial thresholding and morphology bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…The combined cumulative distribution of cIMT error curves for (i) AtheroCloud™ vs. manual, (ii) sonographer vs. manual (iii) AtheroCloud™ vs. sonographer is shown in Figure 10. Keeping the cIMT error threshold as 10% of the cIMT thickness (i.e., nearly 0.11 mm), we observed that 91.15%, 68.31% and 53.91% of population met the error threshold criteria for three error curves.…”
Section: Cumulative Distribution Of Cimt Errors and Li/ma Errorsmentioning
confidence: 87%
See 1 more Smart Citation
“…The combined cumulative distribution of cIMT error curves for (i) AtheroCloud™ vs. manual, (ii) sonographer vs. manual (iii) AtheroCloud™ vs. sonographer is shown in Figure 10. Keeping the cIMT error threshold as 10% of the cIMT thickness (i.e., nearly 0.11 mm), we observed that 91.15%, 68.31% and 53.91% of population met the error threshold criteria for three error curves.…”
Section: Cumulative Distribution Of Cimt Errors and Li/ma Errorsmentioning
confidence: 87%
“…This is beyond the scope for this pilot study. We have however adapted a standardized software (ImgTracer™, AtheroPoint, Roseville, CA, USA), which has been applied to several studies in medical imaging [68][69][70][71][72][73]. …”
mentioning
confidence: 99%
“…Evaluation in 233 CT scans reported a inclusion rate of 92.6% (373 out of 406 juxtapleural nodules), with averages of under-and oversegmentation of 2.4% and 0.3% respectively. Also, a control feedback system based segmentation using morphology and texture was proposed in [15] for analysis of 96 patients, which 81 had presence of ILDs. This approach obtained a Dice coefficient of 98.21% ± 1.35% and 98.58% ± 1.28% for left and right lungs respectively, with an average of 95.40% for both lungs.…”
Section: A Related Workmentioning
confidence: 99%
“…Hence, a fast and intuitive lung segmentation and visualization method could have remarkable practical significance and clinical value for optimize screening efficiency. Thus far, many lung segmentation methods have been studied by researchers, see [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17] and references therein. Here, we classify them simply into two classes: the automatic segmentation methods and the interactive segmentation methods.…”
Section: Introductionmentioning
confidence: 99%